CARBON SOURCE OPTIMIZATION FOR ANTIBIOTIC PRODUCTION FROM AAPTOS-ASSOCIATED BACTERIA Rhodobacteracea bacterium SP.2.11 - Murniasih, Tutik; Bayu, Asep (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
Marine sponge Aaptos-aaptos is thought to produce antimicrobial aaptamine and its derivatives. To investigate whether its associated bacteria are in fact the producer of such bioactive compounds, a study of antibacterial compounds derived from Aaptos-associated bacteria was conducted. In this research, approximately 10 bacterial colonies were isolated from the sponge Aaptos aaptos. Among the bacteria isolated, the one that showed the most potential for producing antibacterial compounds was Rhodobacteracea bacterium. Extra and intracellular bacterial extract from this strain strongly inhibited the growth of pathogenic bacteria Staphylococcus aureus and Vibrio eltor, while were moderately effective against Bacillus subtilis. Optimization of antibacterial activity was conducted by culturing Rhodobacteraceae bacterium in various carbon sources such as glucose, lactose, amylum, molasses and glycerol. The highest production of biomass was obtained by culturing this bacteria in SYP (Seawater Yeast Peptone) medium, enriched with 1% glycerol as the carbon source and with a harvesting time of around 56-104 hours. The highest activity (8 U/ml) was reached when culturing this strain in SYP medium without any adding of carbon sources. Data analysis using a statistical tool indicated that carbon sources added to medium do not have a significant effect on antibacterial activity. Characterizing the compound responsible for the antibacterial properties will be the topic of further work.Keywords : carbon source, Rhodobacteracea bacterium, Aaptos aaptos, associated bacteria